2013
DOI: 10.1155/2013/686304
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotic‐Like Effect of Trimetazidine in a Rodent Model

Abstract: Trimetazidine (TMZ) has been used as an anti-ischemic agent for angina pectoris, chorioretinal disturbances, and vertigo. Also, it can induce extrapyramidal type adverse reaction such as parkinsonism, gait disorder, and tremor via blockade of D2 receptors. In the present study, we evaluated the effect of TMZ on novelty-induced rearing behavior and apomorphine-induced stereotypy behavior in male rats. Four groups of rat (n = 7) were administrated with TMZ (10 and 20 mg/kg, i.p.), chlorpromazine (1 mg/kg, i.p.),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…demonstrated modulation of rearing and stereotype behavior due to trimetazidine therapy mediated by mesolimbic dopaminergic effects. [ 12 ]…”
Section: Discussionmentioning
confidence: 99%
“…demonstrated modulation of rearing and stereotype behavior due to trimetazidine therapy mediated by mesolimbic dopaminergic effects. [ 12 ]…”
Section: Discussionmentioning
confidence: 99%
“…Drugs owning a piperazine core can process strong postsynaptic inhibition of dopamine receptors, including dopamine D2 receptors 10 , which are present in many brain structures such as the striatum having a substantial role in regulation of movements. The potential antipsychotic-like effect of TMZ described in a rodent model may also support the hypothesis that TMZ can cross the blood-brain barrier and interact with dopamine receptors in the central nervous system 15 .Based on available findings, the European Medicines Agency (EMA) made a recommendation for the more careful use of TMZ in certain groups of patients and against the application of the drug for the treatment of patients with PD in 2012 16 . However, some recent data show that this recommendation is not followed strictly enough since a not negligible part of TMZ users is still patients with movement disorders diagnosed prior to the prescription of the drug 13 .Although motor symptoms of reversible TMZ-induced parkinsonism have been considered to be mild by previous descriptions 5,7,9,11 , they can have a serious impact on the health-related quality of life (HRQoL) 5 .…”
mentioning
confidence: 79%
“…Among other mechanisms of action, TMZ has been reported to block dopamine D 2 receptors [ 7 ] and increase the serum and platelet levels of serotonin [ 18 ]. Increased brain concentration of serotonin can also modulate seizure processes.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it has been reported that inducible loss of D 2 receptors causes significant motor impairment in mice [ 37 , 38 ]. Bearing in mind the fact that TMZ blocks dopaminergic D 2 receptors [ 7 ], one can assume that the addition of the two mechanisms can trigger motor impairment in animals treated concomitantly with valproate and TMZ. Nevertheless, this hypothesis does not seem to be reliable in light of results for phenobarbital, a potent agonist of the barbiturate site within the GABA-related complex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation